Emergency cervical cerclage in delayed-interval delivery of twin pregnancies: a scoping review - Hong Cui; Huan Li; Zhihua Yin (BMC, 2024)
Abstract Background The protocol for delayed-interval delivery of the second twin in twin pregnancies has not been standardized. Cervical cerclage is often performed, but its use is debated. To conduct a scoping review on cervical cerclage for prolonging the intertwin delivery interval and improving second twin survival and maternal outcomes after preterm delivery or spontaneous abortion of the first twin in twin pregnancies. Methods Seven Chinese and English language databases were searched from inception to March 1, 2023, including PubMed, The Cochrane Library, Web of Science, CNKI, Wanfang Data, VIP Chinese Science Journal Database, and Sinomed. Relevant observational studies that assessed the effectiveness of the use of cervical cerclage in delayed-interval delivery of twins were screened and selected, and raw data were extracted, and descriptive statistics and chi-square analysis were performed. Results A total of 102 articles were retrieved. After screening and exclusion of duplicate and irrelevant articles, 22 articles meeting the inclusion criteria were obtained. Studies in which cerclage was performed reported longer intertwin delivery intervals than those that did not perform cerclage, and the difference was statistically significant. The cerclage group also tended to have lower rates of chorioamnionitis and maternal complications, but the difference between the two groups was not statistically significant. Conclusion After excluding patients with contraindications, emergency cervical cerclage can be considered in cases of spontaneous abortion of the first twin in twin pregnancies to prolong the gestation and improve the prognosis of the remaining fetus until it becomes viable and increases its birth weight.